2021
DOI: 10.1029/2020jb020169
|View full text |Cite
|
Sign up to set email alerts
|

The Geometry of the Subducted Slab Beneath Sumatra Revealed by Regional and Teleseismic Traveltime Tomography

Abstract: Sumatra is located on the western margin of Sundaland (Figure 1). According to plate reconstruction, Sumatra has been situated at its current location since the Late Jurassic (Hall, 2012). With the closure of the Neotethys Ocean, the intra-oceanic Woyla Arc accreted onto the western margin of Sundaland, forming present-day Sumatra (Advokaat et al., 2018; Hall, 2012, 2015) during the Late Cretaceous. Subduction beneath Sumatra was minimal from the Late Cretaceous to the Early Eocene, and Australia remained clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 94 publications
(386 reference statements)
2
12
0
Order By: Relevance
“…These dip direction estimates agree well with the Slab2 model (Figures 6 and 7). The continuous variation of slab dip direction along the Sunda trench (Figure 7c) implies slab folding or tearing, also noted in travel time tomography studies (Liu et al, 2019(Liu et al, , 2021. The slab folding may be a result of the oblique subduction of the Australian plate (Liu et al, 2019;McCaffrey, 2009), or the lateral bending of the Australian plate, which is increasingly driven by gravity on the east side of the Wharton fossil ridge as the plate cools down.…”
Section: Slab Internal Deformationmentioning
confidence: 74%
“…These dip direction estimates agree well with the Slab2 model (Figures 6 and 7). The continuous variation of slab dip direction along the Sunda trench (Figure 7c) implies slab folding or tearing, also noted in travel time tomography studies (Liu et al, 2019(Liu et al, , 2021. The slab folding may be a result of the oblique subduction of the Australian plate (Liu et al, 2019;McCaffrey, 2009), or the lateral bending of the Australian plate, which is increasingly driven by gravity on the east side of the Wharton fossil ridge as the plate cools down.…”
Section: Slab Internal Deformationmentioning
confidence: 74%
“…An important clue is the low‐V zone in the subducted slab beneath Nias Island ( L4 in Figures 10a, 10b, and 11), which is confirmed by our extensive resolution tests (Figures 6c and 6d). Previous studies have suggested the presence of an intra‐slab low‐V zone caused by slab tearing under Toba (Hall & Spakman, 2015; Kong et al., 2020; Liu et al., 2021; Toyokuni et al., 2022), implying a somewhat extensive feature. In contrast, the low‐V anomaly L4 appears as an approximate cylinder with a diameter of ∼3° connecting the subslab mantle with the mantle wedge.…”
Section: Resultsmentioning
confidence: 94%
“…Previous tomographic studies in this region have unveiled the main features of the crust and upper mantle (e.g., Hall & Spakman, 2015;Liu et al, 2021;Toyokuni et al, 2022;Wang, Liu, et al, 2022). However, their low resolution prevented adequate imaging of the detailed structures.…”
Section: Tomographic Images and Tectonic Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We use the teleseismic imaging method based on the eikonal equation to invert the crust-mantle velocity and the radial anisotropy model. The eikonal equation in any heterogeneous medium can be expressed as (Liu et al, 2021):…”
Section: Methodsmentioning
confidence: 99%